Application of polysulfide in lithium metal battery, lithium metal battery and solid-state battery

By adding polysulfide to the electrolyte or polymer electrolyte of lithium metal batteries, the problem of insufficient stability of the interface between the lithium negative electrode and the electrolyte is solved, the mechanical properties and interface stability of the SEI layer are improved, and the cycle life of the battery is significantly improved.

CN119581708APending Publication Date: 2025-03-07EVE ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411752356.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The stability of the interface between the lithium negative electrode and the electrolyte (mass) in lithium metal batteries is insufficient, resulting in an increase in the internal resistance of the battery and a decrease in the circulation performance.

Method used

Polysulfide is added to the electrolyte or polymer electrolyte of lithium metal batteries, and the general structure formula is Li2Sn (2

Benefits of technology

By changing the interface chemical composition of the SEI layer, a sulfur-containing inorganic SEI layer is formed, which improves the interface stability of the electrolyte/mass and metal lithium, reduces the transfer impedance of Li+, promotes uniform deposition of lithium ions and the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581708A_ABST
    Figure CN119581708A_ABST
Patent Text Reader

Abstract

The invention provides application of polysulfide in a lithium metal battery, the lithium metal battery and a solid-state battery. Wherein the polysulfide is used as an electrolyte of a lithium metal battery or an additive of a polymer electrolyte; the structural general formula of the polysulfide is Li2Sn, and n is greater than 2 and less than or equal to 6. Polysulfide can react with lithium metal to generate Li2S2 / Li2S, so that chemical components of an SE I layer interface are changed, a sulfur-containing inorganic SE I layer is formed on the surface of a negative electrode, and the mechanical property of the SE I layer and the interface stability of electrolyte / electrolyte and metal lithium are improved; and the Li2S2 / Li2S can also reduce the transfer impedance of Li < + >, promote the uniform deposition of lithium ions and inhibit the growth of lithium dendrites. And on the other hand, the high polarizability between Li < + > and the polysulfide anion Sn < 2-> can weaken the combination of a solvent or a polymer substrate and Li < + >, accelerate the migration of Li < + > and promote the diffusion rate of Li < + > in the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an application of polysulfide in lithium metal batteries, lithium metal batteries and solid-state batteries. Background Art

[0002] Lithium metal secondary batteries have become a hot topic in the research and development of next-generation batteries due to their high energy density. However, some inherent defects limit the application of lithium metal secondary batteries, such as the stability of the interface between the lithium negative electrode and the electrolyte (substance). The electrolyte (substance) easily reacts with lithium metal at the interface to generate an unstable SE I layer, which will continuously collapse and rebuild during the SE I layer cycle, resulting in the continuous consumption of the electrolyte / substance, the gradual accumulation and thickening of the SE I layer, and the increase of the battery's internal resistance, which directly affects the battery's cycle performance.

[0003] In order to solve the problems of lithium metal negative electrodes, the improvement methods adopted by everyone are mainly focused on electrolyte / quality optimization or negative electrode modification. For example, on the basis of conventional electrolyte / quality, self-synthesized new lithium salts / fluorinated solvents / new polymer matrix materials are introduced to improve the SE I layer composition, or the interface protection layer is introduced by coating / spraying on the surface of the lithium negative electrode. However, the above methods have the problems of poor structural stability of lithium metal negative electrodes, complex process flow, high production cost, and difficulty in mass production. Summary of the invention

[0004] The main purpose of the present application is to provide an application of polysulfide in lithium metal batteries, lithium metal batteries and solid-state batteries to solve the problem of insufficient stability of the interface between the lithium negative electrode and the electrolyte (material) of lithium metal batteries in the prior art.

[0005] In order to achieve the above-mentioned object, according to one aspect of the present application, a use of polysulfide in a lithium metal battery is provided, wherein the polysulfide is used as an additive to the electrolyte or polymer electrolyte of the lithium metal battery; the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0006] Further, the amount of polysulfide added is 0.1%-5% of the mass of the electrolyte; the electrolyte includes at least one of an ester electrolyte, an ether electrolyte and a local high-concentration electrolyte; further, the amount of polysulfide added is 0.5%-2% of the mass of the electrolyte;

[0007] Alternatively, the amount of polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix; the polymer electrolyte matrix includes at least one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene and polymethyl methacrylate; further, the amount of polysulfide added is 0.5%-2% of the mass of the polymer electrolyte matrix.

[0008] Furthermore, the polymer electrolyte further comprises a solvated ionic liquid; the solvated ionic liquid comprises lithium bis(trifluoromethanesulfonyl)imide and an ether solvent, and the ether solvent comprises any one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4);

[0009] Furthermore, the ratio of the solvated ionic liquid to the polymer electrolyte matrix is ​​3-8:2-7.

[0010] Furthermore, the preparation method of the polysulfide comprises: mixing elemental sulfur, lithium sulfide and an organic solvent, heating and stirring to obtain a polysulfide solution;

[0011] Further, the dielectric constant of the organic solvent is greater than or equal to 5, and further, the organic solvent is selected from any one or more of N,N-dimethylacetamide, N-methylacetamide, acetamide, N,N-dimethylformamide, N-methylformamide, formamide, caprolactam, dimethyl sulfoxide, 1,3-dioxolane, ethylene glycol dimethyl ether, malononitrile and tetramethyl urea;

[0012] Furthermore, the concentration of the polysulfide solution is 0.5 mol / L-1 mol / L.

[0013] Furthermore, the stirring temperature is 60-90° C., and the stirring time is 12-24 h.

[0014] Furthermore, the positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel cobalt manganese material and a lithium cobalt oxide material.

[0015] According to another aspect of the present application, a lithium metal battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte contains polysulfide, and the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0016] Furthermore, the amount of polysulfide added is 0.1%-5% of the mass of the electrolyte.

[0017] Furthermore, the amount of polysulfide added is 0.5-2% of the mass of the electrolyte.

[0018] The electrolyte includes at least one of an ester electrolyte, an ether electrolyte and a local high-concentration electrolyte.

[0019] Furthermore, the positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel cobalt manganese material and a lithium cobalt oxide material.

[0020] According to another aspect of the present application, a lithium metal solid-state battery is provided, comprising a positive electrode, a negative electrode and a polymer electrolyte, wherein the polymer electrolyte contains polysulfide, and the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0021] Further, the amount of polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix, and further 0.5%-2%;

[0022] The electrolyte polymer matrix in the polymer electrolyte includes at least one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene and polymethyl methacrylate;

[0023] The polymer electrolyte also includes a solvated ionic liquid; the solvated ionic liquid includes lithium bis(trifluoromethanesulfonyl)imide and an ether solvent, wherein the ether solvent includes any one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4).

[0024] Furthermore, the ratio of the solvated ionic liquid to the polymer electrolyte matrix is ​​3-8:2-7.

[0025] Furthermore, the positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel cobalt manganese material and a lithium cobalt oxide material.

[0026] By using the technical solution of the present application, polysulfide can react with lithium metal to generate Li2S2 / Li2S, which changes the interface chemical composition of the SEI layer, forms a sulfur-containing inorganic SEI layer on the negative electrode surface, improves the mechanical properties of the SEI layer and the interface stability between the electrolyte / substrate and metallic lithium; and Li2S2 / Li2S can also reduce Li + transfer impedance, promoting the uniform deposition of lithium ions and inhibiting the growth of lithium dendrites. + With polysulfide anion S n 2- The high polarizability between (2<n≤6) will weaken the solvent or polymer substrate and Li + The combination of Li + Migration of Li +Diffusion rate in the battery. When polysulfides are added to the electrolyte of the solid-state battery, the conductivity of the electrolyte can be improved and the crystallinity of the electrolyte matrix can be reduced, thereby further improving the electrochemical performance and stability of the solid-state battery. At the same time, the researchers of this application have found through a large number of studies that the application of the above-mentioned polysulfides as additives in lithium metal batteries can also significantly improve the battery cycle life. This application adds polysulfides to the electrolyte or polymer electrolyte of the lithium metal battery, so that the lithium metal battery not only has a higher energy density, but also has a higher capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0028] Figure 1 XRD patterns of the PEO matrix and the solid electrolyte according to Example 1 of the present application and the solid electrolyte of Comparative Example 6 are shown. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0031] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values ​​of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0032] As analyzed in the background technology of this application, there is a problem in the prior art that the interface between the lithium negative electrode and the electrolyte (substance) of the lithium metal battery is insufficiently stable. In order to solve this problem, this application provides an application of polysulfide in lithium metal batteries, lithium metal batteries and solid-state batteries.

[0033] According to a typical embodiment of the present application, a polysulfide is provided for use in a lithium metal battery, wherein the polysulfide is used as an additive to an electrolyte or a polymer electrolyte of a lithium metal battery; the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0034] The above polysulfides can react with lithium metal to generate Li2S2 / Li2S, which changes the interface chemical composition of SE I layer, forms a sulfur-containing inorganic SEI layer on the negative electrode surface, improves the mechanical properties of SE I layer and the interface stability between electrolyte / substrate and metallic lithium; and Li2S2 / Li2S can also reduce Li + transfer impedance, promoting the uniform deposition of lithium ions and inhibiting the growth of lithium dendrites. + With polysulfide anion S n 2- The high polarizability between (2<n≤6) will weaken the solvent or polymer substrate and Li + The combination of Li + Migration of Li +Diffusion rate in the battery. When polysulfides are added to the electrolyte of the solid-state battery, the conductivity of the electrolyte can be improved and the crystallinity of the electrolyte matrix can be reduced, thereby further improving the electrochemical performance and stability of the solid-state battery. At the same time, the researchers of this application have found through a large number of studies that the application of the above-mentioned polysulfides as additives in lithium metal batteries can also significantly improve the battery cycle life. This application adds polysulfides to the electrolyte or polymer electrolyte of the lithium metal battery, so that the lithium metal battery not only has a higher energy density, but also has a higher capacity retention rate.

[0035] The lithium metal battery of the present application refers to a battery whose negative electrode material is lithium or a lithium alloy, wherein the lithium alloy is an alloy material of lithium and any one or more of boron, silicon, tin, silver, indium, magnesium, copper, zinc, titanium and aluminum.

[0036] In addition, polysulfides can reduce the crystallinity of polymer electrolytes and improve ionic conductivity. Through the action of hydrogen bonds, they form strong interactions with hydrogen atoms in the -OCH2CH2O- unit of the polymer electrolyte matrix, such as PEO, which interferes with the transfer of electrons from proton to proton in -OCH2CH2O-, weakens the spin-spin interaction, and thus inhibits the regular arrangement of polymer chain segments and reduces crystallinity.

[0037] The polysulfide additive has no special requirements for other components in the electrolyte or polymer electrolyte of the lithium metal battery, and those skilled in the art can select from the prior art. As an example, the electrolyte includes but is not limited to at least one of an ester electrolyte, an ether electrolyte, and a local high-concentration electrolyte; the polymer electrolyte matrix includes but is not limited to at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PEO), and polymethyl methacrylate (PMMA).

[0038] The general structural formula of the above polysulfide is Li2S n In the example, the value of n can be 3, 4, 5, or 6.

[0039] In some embodiments of the present application, the amount of polysulfide added is 0.1%-5% of the mass of the electrolyte. For example, the amount of polysulfide added is 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.7% of the mass of the electrolyte, but not limited thereto; in some embodiments of the present application, the amount of polysulfide added is 0.5%-2% of the mass of the electrolyte. When the above-mentioned polysulfide is used as an additive to the electrolyte, the polysulfide can be directly used after being uniformly mixed with other components of the electrolyte, and the liquid can be injected in the existing manner.

[0040] In some embodiments of the present application, the amount of polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix; as an example, the amount of polysulfide added is 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.7% of the mass of the polymer electrolyte matrix, but not limited thereto; in some embodiments, the amount of polysulfide added is 0.5%-3%, preferably 0.5%-2% of the mass of the polymer electrolyte matrix. The above additives are mixed with the polymer solid electrolyte raw materials and cast-filmed for battery assembly and preparation.

[0041] In some embodiments of the present application, the above-mentioned polymer electrolyte also includes a solvated ionic liquid; the solvated ionic liquid includes lithium bis(trifluoromethanesulfonyl)imide and an ether solvent, and the ether solvent includes: any one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4).

[0042] In some embodiments of the present application, the ratio of the solvated ionic liquid to the polymer electrolyte matrix is ​​3-8:2-7.

[0043] The polysulfide conforming to the above structural formula can be selected from the prior art. In some embodiments of the present application, the preparation method of the polysulfide includes: mixing elemental sulfur, lithium sulfide and an organic solvent, heating and stirring to obtain a polysulfide solution. In some embodiments of the present application, the concentration of the polysulfide in the polysulfide solution is 0.5 mol / L-1 mol / L.

[0044] In some embodiments of the present application, the dielectric constant of the organic solvent is greater than or equal to 5, which can promote the dissolution of polysulfides. Exemplarily, the organic solvent is selected from any one or more of N, N-dimethylacetamide, N-methylacetamide, acetamide, N, N-dimethylformamide, N-methylformamide, formamide, caprolactam, dimethyl sulfoxide, malononitrile, 1,3-dioxolane, ethylene glycol dimethyl ether, and tetramethyl urea. In some embodiments of the present application, the stirring temperature is 60-90°C and the stirring time is 12-24h.

[0045] According to the polysulfide Li2S n The value of n in the formula (a) determines the molar ratio of elemental sulfur S to lithium sulfide Li2S. In some embodiments of the present application, the molar ratio of elemental sulfur S to lithium sulfide Li2S is (3-5):1.

[0046] The polysulfide solution prepared by the above method can be directly added to the electrolyte, or directly used in the preparation of the polymer electrolyte, and can be converted into a corresponding ratio.

[0047] When the above-mentioned polysulfide is used as an additive for the electrolyte or polymer electrolyte of a lithium metal battery, there is no special requirement for the material selection and preparation method of other components of the lithium metal battery (such as the positive electrode, the negative electrode or the separator), and technicians in this field can choose from the existing technology.

[0048] In some embodiments of the present application, the positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel cobalt manganese material and a lithium cobalt oxide material. When a lithium metal secondary battery is prepared using an electrolyte or a polymer electrolyte containing the above-mentioned polysulfide, it has better cycle performance and higher stability and safety.

[0049] According to another typical embodiment of the present application, a lithium metal battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte contains polysulfide, and the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0050] The above polysulfides can react with lithium metal to generate Li2S2 / Li2S, which changes the interface chemical composition of the SE I layer, forms a sulfur-containing inorganic SE I layer on the negative electrode surface, improves the mechanical properties of the SE I layer and the interface stability between the electrolyte and metallic lithium; and Li2S2 / Li2S can also reduce the Li + transfer impedance, promoting the uniform deposition of lithium ions and inhibiting the growth of lithium dendrites. + With polysulfide anion S n 2- The high polarizability between (2<n≤6) will weaken the solvent and Li+ The combination of Li + Migration of Li + The diffusion rate in the battery. Therefore, the lithium metal battery containing the above polysulfide in the electrolyte has good stability and cycle performance. At the same time, the researchers of this application also found that the cycle life of the lithium metal battery containing the above polysulfide as an additive has also been significantly improved.

[0051] In some embodiments of the present application, the amount of polysulfide added is 0.1%-5% of the mass of the electrolyte. For example, the amount of polysulfide added is 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.7% of the mass of the electrolyte, but is not limited thereto. In some embodiments, the amount of polysulfide added is 0.5-2% of the mass of the electrolyte. It will be understood by those skilled in the art that the above amount does not include the solvent of the polysulfide solution.

[0052] In some embodiments of the present application, the electrolyte includes at least one of an ester electrolyte, an ether electrolyte and a local high-concentration electrolyte.

[0053] In some embodiments of the present application, the electrolyte includes, by mass percentage, 10%-20% of lithium salt, 80.5%-85% of organic solvent and 0.1%-5% of additives, wherein the additives include the polysulfide mentioned above.

[0054] By way of example, the lithium salts include but are not limited to any one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB) and lithium difluorooxalatoborate (LiODFB).

[0055] As an example, the organic solvent includes an ester solvent or an ether solvent, wherein the ester solvent includes but is not limited to ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethyl butyrate, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroethyl carbonate or di(2,2,2-trifluoroethyl) carbonate. Ethers include but are not limited to tetrahydrofuran (THF), 2-methyltetrahydrofuran (2me-thf), 1,3-dioxolane (DOL), dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4) and diethylene glycol dimethyl ether (DG).

[0056] In some embodiments of the present application, the positive electrode active material of the above-mentioned lithium metal battery is at least one of lithium iron phosphate material, ternary nickel cobalt manganese material and lithium cobalt oxide material, which is beneficial to further improve the performance of the lithium metal battery.

[0057] As an example, the negative electrode material of a lithium metal battery can be lithium, lithium silicon alloy material, lithium tin alloy material, etc.

[0058] According to another typical embodiment of the present application, a lithium metal solid-state battery is provided, comprising a positive electrode, a negative electrode and a polymer electrolyte, wherein the polymer electrolyte contains polysulfide, and the general structural formula of the polysulfide is Li2S n , where 2<n≤6.

[0059] The above polysulfides can react with lithium metal to generate Li2S2 / Li2S, which changes the interface chemical composition of SE I layer, forms a sulfur-containing inorganic SEI layer on the negative electrode surface, improves the mechanical properties of SE I layer and the interface stability between polymer electrolyte and metal lithium; Li2S2 / Li2S can also reduce Li + transfer impedance, promoting the uniform deposition of lithium ions and inhibiting the growth of lithium dendrites. + With polysulfide anion S n 2- The high polarizability between (2<n≤6) will weaken the polymer substrate and Li + The combination of Li + Migration of Li +Diffusion rate in the battery. When polysulfides are added to the electrolyte of the solid-state battery, the conductivity of the electrolyte can be increased and the crystallinity of the electrolyte matrix can be reduced, thereby further improving the electrochemical performance and stability of the solid-state battery. At the same time, the researchers of this application also found that the cycle life of the solid-state lithium metal battery containing the above-mentioned polysulfides as additives can be significantly improved.

[0060] In addition, polysulfides can reduce the crystallinity of polymer electrolytes and improve ionic conductivity. Taking PEO electrolyte as an example, through the action of hydrogen bonds, they form strong interactions with the hydrogen atoms in the -OCH2CH2O- unit in PEO, interfering with the transfer of electrons from proton to proton in -OCH2CH2O-, weakening the spin-spin interaction, thereby inhibiting the regular arrangement of polymer chain segments and reducing crystallinity.

[0061] In some embodiments of the present application, the amount of polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix. For example, the amount of polysulfide added is 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.7% of the mass of the polymer electrolyte matrix, but is not limited to this. In some embodiments, the amount of polysulfide added is 0.5%-3%, preferably 0.5%-2%, of the mass of the polymer electrolyte matrix.

[0062] In some embodiments of the present application, the polymer electrolyte matrix in the above-mentioned polymer electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polymethyl methacrylate (PMMA).

[0063] The above-mentioned polymer electrolyte may also include a lithium salt, and the type of lithium salt may be selected from the prior art, such as any one or more of lithium hexafluorophosphate (Li PF6), lithium perchlorate (Li C l O4), lithium tetrafluoroborate (Li BF4), lithium bis(fluorosulfonyl)imide (Li FS I), lithium bis(trifluoromethanesulfonyl)imide (Li TFS I), lithium bis(oxalatoborate) (Li BOB) and lithium difluorooxalatoborate (LiODFB).

[0064] The above-mentioned polymer electrolyte may also include other substances besides the polysulfide having the above-mentioned general formula, so that the polymer solid electrolyte has suitable ionic conductivity and electrochemical stability window, and supports ion transport and stable operation of the battery at room temperature. In some embodiments of the present application, the polymer electrolyte also includes a solvated ionic liquid; the solvated ionic liquid includes lithium bistrifluoromethanesulfonyl imide (Li TFS I) and an ether solvent, wherein the ether solvent includes any one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4); in some embodiments, the ratio of the solvated ionic liquid to the polymer matrix is ​​3-8:2-7.

[0065] In some embodiments of the present application, the positive electrode active material of the lithium metal battery is at least one of lithium iron phosphate material, ternary nickel cobalt manganese material and lithium cobalt oxide material, which can further improve the cycle performance and service life of the lithium metal solid-state battery.

[0066] The material of the negative electrode sheet is lithium or a lithium alloy, wherein the lithium alloy is an alloy material of lithium and any one or more of boron, silicon, tin, silver, indium, magnesium, copper, zinc, titanium and aluminum.

[0067] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.

[0068] Example 1

[0069] Preparation of polysulfides

[0070] Elemental sulfur and lithium sulfide Li2S were dissolved in a DOL / DME mixed solvent (the volume ratio of DOL and DME was 1:1) at a molar ratio of 5:1, and stirred at 90°C for 24 hours to obtain a polysulfide Li2S6 solution with a concentration of 0.5 mol / L.

[0071] Preparation of polymer solid electrolyte

[0072] 1) TEGDME (G4) and Li TFS I were mixed in a molar ratio of 1:1 and stirred at 60 °C for 8 h to obtain [Li (G4) 1] [TFS I] (denoted as LG).

[0073] 2) Take an appropriate amount of polymer PEO and dissolve it in the organic solvent acetonitrile. Then add the prepared solvated ionic liquid LG and stir at 60°C for 12 hours to form a uniform solution (denoted as PEO / LG), wherein the ratio of the solvated ionic liquid LG to the polymer matrix PEO is 7:3.

[0074] 3) The polysulfide Li2S6 solution was then added to PEO / LG and stirred at 60°C to obtain a solid electrolyte slurry, in which the mass content of polysulfide was 1%, that is, the mass ratio of polysulfide (without solvent) to polymer PEO matrix (without organic solvent acetonitrile) was 1:100. A partially prepared solid electrolyte slurry sample (denoted as ELGS) and a polymer PEO solution (denoted as PEO) were poured into a polytetrafluoroethylene mold, dried, and then subjected to XRD testing. The test curve is shown in FIG. Figure 1 shown.

[0075] 4) Cut the LFP positive electrode into discs with a diameter of 16 mm, then pour the solid electrolyte slurry onto the LFP positive electrode, let it stand to defoam and dry.

[0076] Assembling the battery

[0077] In a glove box, a composite LFP positive electrode, a lithium sheet, and nickel foam are stacked in sequence and sealed in a button-type battery case to assemble a solid-state battery.

[0078] Example 2

[0079] The difference from Example 1 is that in the process of preparing polysulfide, the molar ratio of elemental sulfur and lithium sulfide Li2S is 2:1, and the obtained polysulfide is Li2S3.

[0080] Example 3

[0081] The difference from Example 1 is that in the process of preparing polysulfide, the molar ratio of elemental sulfur and lithium sulfide Li2S is 3:1, and the obtained polysulfide is Li2S4.

[0082] Example 4

[0083] The difference from Example 1 is that in the process of preparing polysulfide, the molar ratio of elemental sulfur to lithium sulfide Li2S is 4:1, and the obtained polysulfide is Li2S5.

[0084] Example 5

[0085] The difference from Example 1 is that the mass ratio of polysulfide (containing no solvent) to polymer PEO matrix (containing no organic solvent acetonitrile) in the polymer solid electrolyte is 5:100.

[0086] Example 6

[0087] The difference from Example 1 is that the mass ratio of polysulfide (containing no solvent) to polymer PEO matrix (containing no organic solvent acetonitrile) in the polymer solid electrolyte is 0.1:100.

[0088] Example 7

[0089] The difference from Example 1 is that the mass ratio of polysulfide (containing no solvent) to polymer PEO matrix (containing no organic solvent acetonitrile) in the polymer solid electrolyte is 3:100.

[0090] Example 8

[0091] The difference from Example 1 is that the mass ratio of polysulfide (containing no solvent) to polymer PEO matrix (containing no organic solvent acetonitrile) in the polymer solid electrolyte is 2:100.

[0092] Example 9

[0093] The difference from Example 1 is that the mass ratio of polysulfide (containing no solvent) to polymer PEO matrix (containing no organic solvent acetonitrile) in the polymer solid electrolyte is 0.5:100.

[0094] Example 10

[0095] Preparation of electrolyte

[0096] Add the same polysulfide Li2S6 solution as in Example 1 to the ether electrolyte (Li FS I / DME / TTE), wherein Li2S6 accounts for 1% of the total mass of the electrolyte, and heat and stir to mix evenly.

[0097] Assembling the battery

[0098] In the glove box, stack LFP positive electrode-electrolyte-diaphragm-electrolyte-lithium sheet-gasket-spring in the order and seal them in a button-type battery shell.

[0099] Embodiment 11

[0100] The difference from Example 10 is that the mass content of polysulfide in the electrolyte is 0.1%.

[0101] Example 12

[0102] The difference from Example 10 is that the mass content of polysulfide in the electrolyte is 5%.

[0103] Comparative Example 1

[0104] The difference from Example 1 is that Li2S6 is replaced by Li2SO4 in the same mass ratio.

[0105] Comparative Example 2

[0106] The difference from Example 1 is that Li2S6 is replaced by Li2PO2F2 in the same mass ratio.

[0107] Comparative Example 3

[0108] The difference from Example 1 is that Li2S6 is replaced by Li2BF4 in the same mass ratio.

[0109] Comparative Example 4

[0110] The difference from Example 1 is that Li2S6 is replaced by LiFSI in the same mass ratio.

[0111] Comparative Example 5

[0112] The difference from Example 1 is that no polysulfide is added to the polymer solid electrolyte.

[0113] Comparative Example 6

[0114] The difference from Example 10 is that no polysulfide is added to the electrolyte.

[0115] A portion of the solid electrolyte slurry sample (referred to as ELG) prepared in the comparative example was poured into a polytetrafluoroethylene mold and dried, and then an XRD test was performed. The test curve is shown in FIG. Figure 1 shown.

[0116] The batteries prepared in the above examples and comparative examples were subjected to cycle performance tests, and the test results are listed in Table 1.

[0117] Electrochemical performance: Under room temperature conditions, 0.1C constant current charging to 4.3V, standing for 5min, 0.1C constant current discharge to 2.5V, standing for 5min, and cycled 100 times to obtain the capacity retention rate.

[0118] Table 1

[0119]

[0120]

[0121] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects: the above polysulfide can react with lithium metal to generate Li2S2 / Li2S, which changes the interface chemical composition of the SE I layer, forms a sulfur-containing inorganic SEI layer on the surface of the negative electrode, and improves the mechanical properties of the SEI layer and the interface stability between the electrolyte / substance and metallic lithium; and Li2S2 / Li2S can also reduce Li + transfer impedance, promoting the uniform deposition of lithium ions and inhibiting the growth of lithium dendrites. + With polysulfide anion S n 2- The high polarizability between (2<n≤6) will weaken the solvent or polymer substrate and Li + The combination of Figure 1It can be seen from the XRD spectrum that the addition of polysulfide Li2S6 (codenamed ELGS) has a lower crystallinity than the ELG electrolyte (PEO+LG) and pure PEO matrix without adding polysulfide, which accelerates the Li + Migration of Li + Diffusion rate in the battery. At the same time, the researchers of this application also found that applying the above polysulfide as an additive to lithium metal batteries can also significantly improve the battery cycle life.

[0122] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.

[0123] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of this application.

[0124] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An application of polysulfide in lithium metal batteries, characterized in that: The polysulfide is used as an additive to the electrolyte or polymer electrolyte of the lithium metal battery; The general structural formula of the polysulfide is Li2S n , where 2<n≤6.

2. The use according to claim 1, characterized in that: The added amount of the polysulfide is 0.1%-5% of the mass of the electrolyte; the electrolyte includes at least one of an ester electrolyte, an ether electrolyte and a local high-concentration electrolyte; preferably, the added amount of the polysulfide is 0.5%-2% of the mass of the electrolyte.

3. The use according to claim 1, characterized in that: The amount of the polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix; the polymer electrolyte matrix includes at least one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene and polymethyl methacrylate; Preferably, the added amount of the polysulfide is 0.5%-2% of the mass of the polymer electrolyte matrix.

4. The use according to claim 3, characterized in that: The polymer electrolyte further comprises a solvated ionic liquid; the solvated ionic liquid comprises lithium bis(trifluoromethanesulfonyl)imide and an ether solvent, and the ether solvent comprises any one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4); Preferably, the ratio of the solvated ionic liquid to the polymer electrolyte matrix is ​​3-8:2-7.

5. The use according to claim 1, characterized in that: The preparation method of the polysulfide comprises: mixing elemental sulfur, lithium sulfide and an organic solvent, heating and stirring to obtain a polysulfide solution; Preferably, the stirring temperature is 60-90° C., and the stirring time is 12-24 h.

6. The use according to claim 5, characterized in that: The dielectric constant of the organic solvent is greater than or equal to 5. Preferably, the organic solvent is selected from any one or more of N,N-dimethylacetamide, N-methylacetamide, acetamide, N,N-dimethylformamide, N-methylformamide, formamide, caprolactam, dimethyl sulfoxide, 1,3-dioxolane, ethylene glycol dimethyl ether, malononitrile and tetramethyl urea; Preferably, the concentration of the polysulfide solution is 0.5 mol / L-1 mol / L.

7. A lithium metal battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The electrolyte contains polysulfide, The general structural formula of the polysulfide is Li2S n , where 2<n≤6.

8. The lithium metal battery according to claim 7, characterized in that The amount of polysulfide added is 0.1%-5% of the mass of the electrolyte, preferably 0.5-2%; The electrolyte includes at least one of an ester electrolyte, an ether electrolyte and a local high-concentration electrolyte; The positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel-cobalt-manganese material and a lithium cobalt oxide material.

9. A lithium metal solid-state battery, comprising a positive electrode, a negative electrode and a polymer electrolyte, characterized in that: The polymer electrolyte contains polysulfide, The general structural formula of the polysulfide is Li2S n , where 2<n≤6.

10. The lithium metal solid-state battery according to claim 9, characterized in that: The amount of polysulfide added is 0.1%-5% of the mass of the polymer electrolyte matrix, preferably 0.5%-2%; The polymer electrolyte matrix in the polymer electrolyte comprises at least one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene and polymethyl methacrylate; The polymer electrolyte further comprises a solvated ionic liquid; the solvated ionic liquid comprises lithium bis(trifluoromethanesulfonyl)imide and an ether solvent, wherein the ether solvent comprises any one of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), and tetraethylene glycol dimethyl ether (G4); preferably, the ratio of the solvated ionic liquid to the polymer electrolyte matrix is ​​3-8:2-7; The positive electrode active material of the lithium metal battery is at least one of a lithium iron phosphate material, a ternary nickel-cobalt-manganese material and a lithium cobalt oxide material.

Citation Information

Patent Citations

  • A cell or battery with a metal lithium electrode and electrolytes therefor

    CN101501897A

  • Electrolyte additive and application thereof

    CN105870502A

  • High-voltage ether electrolyte for lithium metal battery

    CN116759650A

  • Dry manufacturing process with electrolyte additive for the production of a separator and / or an electrode for a lithium cell

    DE102017204826A1

  • Electrolyte comprising lithium polysulfide for lithium air battery, and lithium air battery

    KR1020180025581A